OPTIMISATION OF THE COMPOSITION OF BOARDS MADE FROM WHEAT STRAW AND SAWDUST FROM THE WOOD OF BEECH AND SPRUCE (Innovation in Woodworking Industry and Engineering design, 2026)
The utilization of wood waste for the production of boards or other composite products and their combination with different agricultural lignocellulosic raw materials has become more and more popular.For the purpose of this study, boards were produced from mixtures of wheat straw and sawdust from the wood of beech and spruce. The following properties of the boards have been determined: bending strength, perpendicular tensile strength, water absorption and swelling in thickness. The method of SHEFFE simplex grid plans has been used for the optimisation of boards‟ composition and graphs „composition-property‟ have been drawn up. Conclusions about the possibilities for inclusion of up to 33% wheat straw in the composition of particleboards, produced from waste raw material while maintaining the quality of the end products, have been summarized on the basis of the results from the carried out planned experiments.